ANALISIS KELAYAKAN BUDIDAYA MELON HIDROPONIK DI GREEN HOUSE KEBUN KITA KECAMATAN KANDAT KABUPATEN KEDIRI - Tiara Intan Johar Setyowati; Erlin Widya Fatmawati; Vifi Nurul Choirina (JURNAL ILMIAH NUSANTARA, 2025)
Hydroponics is a modern agricultural innovation that enables plants to grow in a controlled environment, ensuring optimal productivity and quality. Melon (Cucumis melo L.) was selected as the research commodity due to its high economic value and continuously increasing market demand. This study aims to analyze the business feasibility of hydroponic melon cultivation at Green House Kebun Kita in Kediri Regency. The research employed a descriptive quantitative analysis, collecting data on production costs, revenue, and profit, and utilizing financial indicators such as the Revenue Cost Ratio (R/C) and the Break-Even Point (BEP). The findings indicate that the business is profitable and feasible to operate, with a total revenue of IDR 287,000,000 and a net income of IDR 216,160,708 per season. An R/C value of 4.05 and a BEP reached at 474.54 units demonstrate high efficiency. The implication of this study is that hydroponic melon cultivation not only provides a strong prospect for profit but also supports sustainable agricultural practices, provided that cost efficiency and price stability are maintained..